The Influence of Water Quality Based on BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), and DO (Dissolved Oxygen) Values on the Health Level - Hariyono, Hariyono; Yudana, Amarin; Peristiowati, Yuly; Saryono, Hari (Journal of Applied Nursing and Health, 2026)
Background: Poor water quality can have a significant impact on public health. BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), and DO (Dissolved Oxygen) are important indicators of water quality. This study aims to analyze the effects of water quality, as measured by BOD, COD, and DO, on the health status of the Kediri City community. Methods: This study uses an observational quantitative research design with a cross-sectional approach. The sample comprised 100 respondents, selected using a cluster random sampling technique across 3 sub-districts in Kediri City. The data analysis uses a linear regression statistical test to examine the correlation between BOD, COD, and DO values and the health status of the Kediri City community. Results: The study showed that the average BOD value was ± 11.8 mg/L, the average COD value was ± 27.87 mg/L, and the average DO value was ± 4.81 mg/L. For the average health degree based on the water quality of the Kediri city community, the average was ± 30.3 (max. score 40). From statistical analysis, the influence of BOD, COD, and CO levels on the degree of health based on the water quality of the Kediri city community, the data obtained BOD p-value <0.01, COD p-value <0.07, and DO p-value <0.00 (sig. ≤ 0.05). Conclusion: BOD and DO levels influence the degree of health based on water quality in the Kediri city community. At the same time, the COD value does not affect the degree of health based on the water quality of the Kediri city community. This study shows that water quality in the city, as measured by BOD and COD values, still does not meet the Quality Standards, which can have a significant impact on the health of Kediri City's residents.